2007
DOI: 10.1016/j.amjhyper.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Actions of Allylmercaptocaptopril and Captopril in a Rat Model of Metabolic Syndrome

Abstract: Both captopril and allylmercaptocaptopril are effective in attenuating multiple abnormalities of metabolic syndrome. Allylmercaptocaptopril may have additional effectiveness on improving glucose tolerance, further lowering blood pressure, reducing cardiac hypertrophy, preventing weight gain, and protecting against renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…However, the success rate in the intensive medical therapy group did not differ significantly from that of conventional treatment group in the latter years of the follow-up period, and a Kaplan–Meier analysis did not show a significant difference in MetS risk between the treatment groups. Studies in both animals and humans have suggested that treatment with metformin, [28] captopril, [29,30] valsartan, [31,32] simvastatin, [33] or fenofibrate [34,35] alone reduced the development of MetS, which is largely consistent with our findings. Because MetS increases the risk of cardiovascular disease, [3638] it seems unlikely that improvements in MetS indicators contributed to a lower risk of subclinical atherosclerosis in the intensive medical therapy group, compared with that in the conventional treatment group.…”
Section: Discussionsupporting
confidence: 91%
“…However, the success rate in the intensive medical therapy group did not differ significantly from that of conventional treatment group in the latter years of the follow-up period, and a Kaplan–Meier analysis did not show a significant difference in MetS risk between the treatment groups. Studies in both animals and humans have suggested that treatment with metformin, [28] captopril, [29,30] valsartan, [31,32] simvastatin, [33] or fenofibrate [34,35] alone reduced the development of MetS, which is largely consistent with our findings. Because MetS increases the risk of cardiovascular disease, [3638] it seems unlikely that improvements in MetS indicators contributed to a lower risk of subclinical atherosclerosis in the intensive medical therapy group, compared with that in the conventional treatment group.…”
Section: Discussionsupporting
confidence: 91%
“…Adipose tissue from obese individuals is known to be an important endocrine organ capable of contributing to insulin resistance, persistent inflammation, and metabolic and vascular dysfunction via the perturbed adipokine secretion profile [34]. The collective action of garlic extract standardized for organosulfur compounds, ginger extract standardized for gingerols and shogaols, biotin and chromium in METABO may contribute to antiadipogenic, anti-inflammatory actions in conjunction with metabolic health benefits [20,21,36,37,49-51]. The bioactive compounds in garlic, ginger, and raspberry in addition to biotin and chromium have been suggested to modulate high-leverage metabolic pathways with nutrigenomic signaling, including: NF-kB, PPAR-γ, PPAR-α, orexigens, and aforementioned adipocytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, oral ingestion of certain capsaicinoids, (active component of chilli peppers from the genus Capsicum ) has been shown to increase energy expenditure, lipolysis and fat oxidation [15], activate brown adipose tissue [16] and stimulate the systemic release of norepinephrine [15,17]. Bioactive compounds found in the rhizomes of ginger ( Zingiber officinale ) and garlic ( Allium sativum ) extracts have been shown to influence many key features of the metabolic syndrome by modulating adipocytokine secretion from adipose tissue, reducing body fat accumulation, decreasing circulating insulin and markers of systemic inflammation in murine and cell culture models, with similar findings emerging from studies in humans [18-21]. Extracts of Citrus aurantium, standardized for p-synephrine and other bioactive amines have been shown to increase resting metabolic rate and enhance weight loss in human clinical trials [22].…”
Section: Introductionmentioning
confidence: 95%
“…SHROB rats can be identified as obese at about 5 weeks of age together with hyperinsulinemia, slightly elevated blood glucose (Friedman et al 1997), and insulin resistance (Velliquette et al 2002). Spontaneous hypertension usually occurs at w3 months of age and rises progressively; animals also develop cardiac hypertrophy and vascular disease (Ernsberger et al 2007). Thus, one can say that obesity precedes hypertension, but it is difficult to say that obesity is a cause of hypertension in this model.…”
Section: Rat Models Of Obesity and Hypertensionmentioning
confidence: 99%